Understanding gel-to-crystal transitions in supramolecular gels. Issue 30 (20th July 2021) - Giuri, Demetra; Marshall, Libby J.; Wilson, Claire; Seddon, Annela; Adams, Dave J.
Abstract : Most supramolecular gels are stable or assumed to be stable over time, and aging effects are often not studied. Abstract : Most supramolecular gels are stable or assumed to be stable over time, and aging effects are often not studied. However, some gels do show clear changes on aging, and a small number of systems exhibit gel-to-crystal transitions. In these cases, crystals form over time, typically at the expense of the network underpinning the gel; this leads to the gel falling apart. These systems are rare, and little is known about how these gel-to-crystal transitions occur. Here, we use a range of techniques to understand in detail a gel-to-crystal transition for a specific functionalised dipeptide based gelator. We show that the gel-to-crystal transition depends on the final pH of the medium which we control by varying the amount of glucon-δ-lactone (GdL) added. In the gel phase, at low concentrations of GdL, and at early time points with high concentrations of GdL, we are able to show the nanometre scale dimensions of the self-assembled fibre using SAXS; however there is no evidence of molecular ordering of the gel fibres in the WAXS. At low concentrations of GdL, these self-assembled fibres stiffen with time but do not crystallise over the timescale of the SAXS experiment. At high concentrations of GdL, the fibres are already stiffened, and then, as the pH drops further, give way to the presence of crystals which appear to grow preferentially along the direction of the fibre axis. We definitively show therefore that the gel and crystal phase are not the same. Our work shows that many assumptions in the literature are incorrect. Finally, we also show that the sample holder geometry is an important parameter for these experiments, with the rate of crystallisation depending on the holder in which the experiment is carried out.